Hungarian Avant-Garde between East and West: The Exploration of European and Russian Scenic Practices in Ödön Palasovszky’s Stage Productions of the 1920s - Zsuzsanna Kalafatics (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2020)
Experimental theatres led by Ödön Palasovszky stand out among the attempts to renew the Hungarian theatrical culture of the 1920s. He was the central figure of the creative community that worked under different names, but the performances were a result of a collective effort. Contemplating on the nature and possibilities of theatrical art, young experimenting artists set themselves the goal of creating a reflective art that was aimed at creating a new society. In their search of new ways of expression, they turned to various forms of cabaret, revue, compere-entertainer, choral genres, and simultaneous play based on the principle of montage and eurhythmics, and they used many scenic innovations. In this paper, the author focuses on the parallel between the theatrical practices of Palasovszky and theatrical experiments made in the USSR and Germany in the 1920s. The analysis is based on an example of Palasovszky’s avant-garde direction in the staging of Nikolai Evreinov’s monodrama The Theatre of the Soul, a production Palasovszky carried out together with his company Extraordinary Stage (Rendkívüli Színpad). The play by Evreinov was presented only once, on October 3, 1928, during the Happy End evening. Among other things, the article focuses on the design of the stage which was made partly with the contribution of Eva Zeisel (Striker), a Hungarian artist, who worked in the Soviet Union in the 1930s and later became a world-famous ceramist in America. Since the scenery depicting a living organism was presented on the stage as part of the action, the performance can be considered one of the most original experiments in the life of the Hungarian avant-garde theater.